Universities’ contributions to sustainable development’s social challenge: a case study of a social innovation practice - Juliani, Douglas Paulesky (2017)
There is an increasing recognition that dealing with sustainable development need to address the social structures that encourage unsustainable economic and environmental practices. Universities represent important sources of knowledge for addressing sustainable development, but there has been relatively limited consideration of their contributions to these social elements. Drawing on recent interest in social innovation as to conceptualise social change and community development, this paper aims to understand universities' involvement in the process of social innovation, for the particular case of a Brazilian higher education institution. By exploring how universities can contribute to the different stages of the social innovation process, it highlights the capacities that universities have to address the social sustainable development challenge. The paper identifies five characteristics of universities contributions to social innovation and sets out an agenda for future research necessary to understand universities' wider contributions to sustainable development.